18F-FDG PET/CT Parameters for Predicting Prognosis in Esophageal Cancer Patients Treated With Concurrent Chemoradiotherapy. (5th July 2021) - Lee, Seokmo; Choi, Yunseon; Park, Geumju; Jo, Sunmi; Lee, Sun Seong; Park, Jisun; Shim, Hye-Kyung
Background and Aims: This study evaluated the prognostic value of 18 F-fluorodeoxyglucose positron emission tomography with integrated computed tomography ( 18 F-FDG PET/CT) performed before and after concurrent chemoradiotherapy (CCRT) in esophageal cancer. Methods: We analyzed the prognosis of 50 non-metastatic squamous cell esophageal cancer (T1-4N0-2) patients who underwent CCRT with curative intent at Inje University Busan Paik Hospital and Haeundae Paik Hospital from 2009 to 2019. Median total radiation dose was 54 Gy (range 34-66 Gy). Our aim was to investigate the relationship between PET/CT values and prognosis. The primary end point was progression-free survival (PFS). Results: The median follow-up period was 9.9 months (range 1.7-85.7). Median baseline maximum standard uptake value (SUVmax) was 14.2 (range 3.2-27.7). After treatment, 29 patients (58%) showed disease progression. The 3-year PFS and overall survival (OS) were 24.2% and 54.5%, respectively. PFS was significantly lower ( P = 0.015) when SUVmax of initial PET/CT exceeded 10 (n = 22). However, OS did not reach a significant difference based on maximum SUV ( P = 0.282). Small metabolic tumor volume (≤14.1) was related with good PFS ( P = 0.002) and OS ( P = 0.001). Small total lesion of glycolysis (≤107.3) also had a significant good prognostic effect on PFS ( P = 0.009) and OS ( P = 0.025). In a subgroup analysis of 18 patients with follow-up PET/CT, the patients with SUV max ≤3.5 in follow-up PET/CT showed longer PFS ( P = 0.028) than those with a maximum SUV >3.5. Conclusion: Maximum SUV of PET/CT is useful in predicting prognosis of esophageal cancer patients treated with CCRT. Efforts to find more effective treatments for patients at high risk of progression are still warranted.